Effects of multidisciplinary team on emergency care for colorectal cancer patients: A nationwide-matched cohort study. Issue 23 (June 2017) - Liao, Chun-Ming; Kung, Pei-Tseng; Wang, Yueh-Hsin; Tsai, Wen-Chen
Abstract : Abstract: The literature describing the effectiveness of multidisciplinary team (MDT) for the care of colorectal cancer remains unclear. We investigated the effects of MDT care on the quality of colorectal cancer treatment, and the emergency department visit number was used as an indicator. In total, 45, 418 patients newly diagnosed with colorectal cancer from the Taiwan National Health Insurance Research Database (2005–2009) were included. Propensity score matching with a ratio of 1:3 was adopted to reduce differences in characteristics between MDT care participants and non-MDT care participants. After matching, 3039 participation MDT care groups and 9117 nonparticipation groups were included and analyzed with χ 2 and t tests, determine the distribution was similar. Without the control of variables, the percentage difference between participation and nonparticipation MDT care groups in utilization of emergency care was 0.03% ( P > .05). The logistic regression model involving controlled variables demonstrated that odds ratio (OR) by probability of emergency care used for participation MDT care groups within a year of cancer diagnosis was less than that for nonparticipation (OR = 0.87, 95% confidence interval: 0.78–0.96). Large amount data were used and confirmed significant benefits of MDT in colorectal cancer care.